Pola Penerapan Merdeka Belajar Berbasis Pembelajaran Berdiferensiasi Pada Mata Pelajaran Ekonomi di PKBM Tunas Madani Kota Tangerang - Merissa Fermica Iskandar; wulandari; amandasona (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2022)
This study discusses the pattern of implementing independent learning based on differentiated learning in the subject of Economics at PKBM Tunas Madani, Tangerang City. The type of research used is descriptive qualitative research which is often called the naturalistic research model because the research is carried out in natural conditions, then the approach is carried out using a pedagogic approach, then the data is collected by means of observation, interviews and documentation. As for the instrument as a tool used to measure phenomena in research where the research instrument is the researcher himself. Then compile interview guidelines that contain questions, as well as observation guidelines and some documentation related to the object of research. The results showed that the economics learning process at PKBM Tunas Madani Kota Tangerang had implemented differentiated learning and assessment as the application of the independent learning application pattern and the implementation of the independent learning application pattern had a good impact on improving the character and creative power of students, making learning economics education more enjoyable , quality and meaningful. The implications of this research are expected to be in an effort to improve the quality of education and overcome special education problems at PKBM Tunas Madani, Tangerang City.   Keywords : Independent Learning, Differentiated Learning, Economics